Incidence, Clinical Presentation and Outcomes of Paraphenylenediamine (Kala Pathar) Poisoning in Patients Presenting at a Tertiary Care Hospital: a Prospective Study - Usman Shahid Butt, Aftab Alam Tanoli, Aisha Rasheed, Sadaf Nadir, Abdul Samad, Salman Pervaiz Rana (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the demographics, clinical features and outcomes of PPD poisoning in such patients. Design of the Study: It was a prospective study. Place and Duration of Study: In this cross-sectional study, the prospective study data of 47 cases were collected from Department of Forensic Medicine and Toxicology, Loralai Medical College, Loralai. Patients and Methods: From 2019 to 2022, data of 47 cases was taken worth of information were gathered from hospitals’ medical records for this prospective study. Information on the subject’s demographics, ingestion method, clinical features, and mode of administration was recorded using a standardized format. In addition to monitoring mortality rates, hospital stays, tracheostomies, and the efficacy of mechanical ventilation, a number of other metrics were collected. For continuous variables’ means and standard deviations (SDs) were calculated. However, percentages were calculated for categorical variables. Results of the Study: Out of 47 patients, 38 (80.85%) were females and 9 (19.15%) were males. During first year of the study, only six cases were reported while in succeeding years cases increases rise rapidly and reached to fifteen in last year final year of the study. Majority of the patients 16 (34%) belong to age group 20-24 years. Nearly, 85% of the patients belong to the rural areas. Moreover, the rate of PPD poisoning in married women increases alarmingly from one case in 2019 to nine cases in 2019. Practical Implication: Currently, there is limited data available on this poisoning as it has emerged as a new tren in our local hospitals. So, the rationale of this study is to evaluate the clinical presentation and outcome of the PPD poisoning in our part so that effective preventive and treatment strategies can be implemented at the onset which would certainly decrease the morbidity and mortality associated with this deadly poisoning. This study can lay down a base for local administrative authorities to consider formulating a law for strict handling of the PPD poisoning at local level and for education of the population. Conclusion: There is a significant amount of distress and death that comes along with PPD poisoning. In order to effectively handle poisoning situations, doctors must be aware of the clinical features and therapeutic choices. In addition, PPD-containing hair colours should be banned because they are so dangerous. Keywords: Poisoning, Suicide, Hair-Dye, Cervicofacial Edema, Paraphenylenediamine, Kala Pathar